THE ROLE OF MOTIVATION IN LEARNING ENGLISH - Yokubjonova Dilnavozxon Serobjon qizi; Umarova Rayxona Baxromjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the role and importance of motivation in learning English as a foreign language. Motivation is considered one of the key factors that influences learners’ success, interest, and persistence in the learning process. The study highlights different types of motivation, such as intrinsic and extrinsic motivation, and explains how they affect students’ language acquisition, participation, and overall performance. Furthermore, the article discusses the role of teachers in increasing students’ motivation through effective teaching methods, positive learning environments, and encouragement. The research concludes that motivated learners are more active, confident, and successful in mastering English, and motivation significantly contributes to achieving language learning goals.